Potential antioxidant and lipid peroxidation inhibition of Phyllanthus acidus leaf extract in minced pork - Tuyen Thi Kim Nguyen; Chamroon Laosinwattana; Montinee Teerarak; Komkhae Pilasombut (My University, 2017)
This study investigated the effect of extraction solvents on antioxidant bio-active compounds as well as potential antioxidant and lipid peroxidation inhibition of Phyllanthus acidus (P. acidus) leaf extract in minced pork.The effect of various solvent systems of water, 25%, 50%, 75% (v/v) ethanol in water and absolute ethanol on the extraction crude yield, total phenolic content, total flavonoid content and in vitro antioxidant activities of P. acidus leaves was determined. In addition, antioxidant activities of the addition of crude extract from P. aciuds leaves at 2.5 and 5 g/kg in minced pork on 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging, 2,2'-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) radical cation decolorization, reducing power and inhibition of lipid peroxidation (thiobarbituric acid reactive substances; TBARS) were determined. Moreover, sensory evaluation of the samples was undertaken by using a 7-point hedonic scale.The results showed that the highest crude yield (2.8 g/100 g dry weight) was obtained from water which also had the highest recovery yield for total phenolic content, total flavonoid content and the strongest antioxidant activity. The addition of crude water extract from P. acidus leaves was more effective in retarding lipid peroxidation and higher antioxidant activity than control and butylated hydroxytoluene in minced pork. In particular, the samples containing P. acidus extract had no significant effect on the sensory scores of overall appearance, color, odor, texture, flavor, and overall acceptability compared to the control.Water solvent was an optimally appropriate solvent for P. acidus leaf extraction because of its ability to yield the highest amount of bio-active compounds and in vitro antioxidant property. Particularly, P. acidus crude water extract also strongly expressed the capacity to retard lipid oxidation, radical scavenging, radical cation decolorization and reducing power in minced pork. The results of this study indicated that P. acidus leaf extract could be used as natural antioxidant in the pork industry.
Keywords: Phyllanthus; Phytochemistry and Bioactivity Studies